ANALISIS SIFAT MEKANIK MATERIAL KOMPOSIT BERPENGUAT SERAT KARBON - Kajang, Gideon; Fahar, Andi Abustan (JNSTA ADPERTISI JOURNAL, 2024)
This research aims to determine the tensile, Young's modulus and shear modulus values ​​through tensile testing using carbon fiber composite materials. In the tensile test, it was found that the tensile value increased in each variation, namely in the 3 layer and 5 layer variations with a percentage of 18.71% in the 3 layer variation and 48.51% in the 5 layer variation. The Young's Modulus value decreased with each variation, namely the 3 layer variation experienced a percentage decrease of 35.01% and the 5 layer variation experienced a percentage decrease of 9.2%.